Current status of vocational delay of gratification among practicing nursing students and its influencing factors: a cross-sectional study - Tianyu Chu; Xian Chen; Qian Zhang; Juanjuan Yang; Hui Zhou; Yibo Wu; Jie Jiao (BMC Nursing)
Abstract Background Practicing nursing students play a critical role in addressing the nursing workforce shortage. Their vocational delay of gratification influences career planning and practice quality. This study aimed to assess the level of vocational delay of gratification among nursing students and identify its influencing factors. Methods A convenience sample of 250 nursing students practicing in three tertiary hospitals in Anhui Province (February–May 2024) was studied. Data were collected using a general information questionnaire, job involvement scale, clinical communication ability scale, and vocational delay of gratification scale. Random forest, independent samples t-test, analysis of variance (ANOVA), and multiple linear regression analyses were applied to identify the key influencing factors. Results There were 39 (15.6%) males and 211 (84.4%) females who participated in this study and the mean score for vocational delay of gratification was (2.843 ± 0.513), the mean score for level of job involvement was (2.468 ± 0.923), and the mean score for ability to communicate with patients was (2.830 ± 1.083).Influencing factors included willingness to upgrade education, whether you are willing to work in nursing after graduation, whether a relative works in a medical facility, ability to communicate with patients, intention to study nursing, level of job involvement(P<0.05). Conclusion Nursing students demonstrated a moderate-to-high level of vocational delay of gratification. Training programs addressing these factors can enhance students’ capabilities, improve internship quality, and support long-term career development. The study conducted in three hospitals in Anhui Province may limit the generalizability of the results due to regional differences in education and practice. Nonetheless, this study provides important insights for optimizing the career development and retention of nursing interns. Trial registration No medical interventions were administered to human participants in this study. Clinical trial number: not applicable.